2017
DOI: 10.1021/acsami.7b07890
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide: A New Carrier for Slow Release of Plant Micronutrients

Abstract: The environmental problems and low efficiency associated with conventional fertilizers provides an impetus to develop advanced fertilizers with slower release and better performances. Here, we report of development of a new carrier platform based on graphene oxide (GO) sheets that can provide a high loading of plant micronutrients with controllable slow release. To prove this concept, two micronutrients, zinc (Zn) and copper (Cu), were used to load on GO sheets and hence formulate GO-based micronutrients ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
114
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(117 citation statements)
references
References 69 publications
3
114
0
Order By: Relevance
“…Recent studies have shown that graphene is a promising material that could serve as a carrier for plant nutrients. It is capable of slow and controlled release of nutrient for the plants benefit, and ultimately increases the amount of crop production with low environmental impact [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that graphene is a promising material that could serve as a carrier for plant nutrients. It is capable of slow and controlled release of nutrient for the plants benefit, and ultimately increases the amount of crop production with low environmental impact [5].…”
Section: Introductionmentioning
confidence: 99%
“…As we know, most controlled release urea either needs to be prepared in water or water‐assisted. [25a,b] Tribochemistry might prepare controlled release urea in a simple and water‐free method. Owing to MPNs pH‐dependent, stability, and porous structure, TA‐M‐urea may be good in high urea content, stability, and controlled release properties.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, MPNs films can be designed potentially in a lot of useful applications, such as patterning, antifouling in marine, and preparation of pH‐dependent capsules (≈30 nm). Inspired by slow release coated fertilizers, water‐soluble urea could encapsulate in a TA‐M coating via ball milling to demonstrate their potential use as a controlled release system . This work provides a new approach to prepare functional coatings with tunable thickness and a versatile platform for preparing green, sustainable, and industrially acceptable controlled release systems, which could shed light on the rational design and synthesis of novel MPNs with on‐demand properties.…”
Section: Introductionmentioning
confidence: 99%
“…Various materials have been developed recently to be used as carriers of pesticide and fertilizer, such as organic polymers, [ 13 ] bio‐sourced matrices, [ 14 ] and inorganic materials. [ 15,16 ] However, most of them only provide individual function and are accompanied by complex preparation processes. Furthermore, they are very susceptible to being washed away by rain, which limit their real applications.…”
Section: Introductionmentioning
confidence: 99%